Food as the basis for development and security: A strategy for Yemen - Breisinger, Clemens; Ecker, Olivier; Funes, José; Yu, Bingxin (International Food Policy Research Institute, 2010)
Yemen has been facing severe development challenges in recent years, but rapidly depleting oil and water resources combined with large population increases and a lack of job-creating growth are making a difficult situation even more complicated. In order to provide opportunities for Yemenis to escape the current situation of widespread poverty and food insecurity, the Government of the Republic of Yemen, under the leadership of the Ministry of Planning and International Cooperation, has developed a strategy to help all Yemeni people gain access to sufficient and nutritious foods in order to live active, productive, and healthy lives. The main objectives of the National Food Security Strategy, developed with the support of the International Food Policy Research Institute, are to (1) cut food insecurity by one-third by 2015, (2) reach moderate food security levels—meaning 90 percent of people have enough to eat year-round—by 2020, and (3) reduce child malnutrition by at least one percentage point per year. As a contribution to this process, the authors of this paper identify seven priority actions to help achieve these goals.